Steric structure–activity relationship of cyproheptadine derivatives as inhibitors of histone methyltransferase Set7/9. Issue 18 (15th September 2016) - Fujiwara, Takashi; Ohira, Kasumi; Urushibara, Ko; Ito, Akihiro; Yoshida, Minoru; Kanai, Misae; Tanatani, Aya; Kagechika, Hiroyuki; Hirano, Tomoya
Graphical abstract: Abstract: Set7/9 is a histone lysine methyltransferase, but it is also thought to be involved in a wide variety of pathophysiological functions. We previously identified cyproheptadine, which has a characteristic butterfly-like molecular conformation with bent tricyclic dibenzosuberene and chair-form N -methylpiperidine moieties, as a Set7/9 inhibitor. In this work, we synthesized several derivatives in order to examine the steric structure–inhibitory activity relationship. We found that even a small change of molecular shape due to reduction or replacement of the 10, 11-olefinic bond of the tricyclic ring generally resulted in a drastic decrease of the inhibitory activity. Our results should be useful not only for development of more potent and selective inhibitors, but also for the construction of novel inhibitor scaffolds.